2016
DOI: 10.1038/ng.3605
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of the α-globin super-enhancer in vivo

Abstract: Many genes determining cell identity are regulated by clusters of mediator-bound enhancer elements collectively referred to as super-enhancers. These have been proposed to manifest higher-order properties important in development and disease. Here, we report a comprehensive functional dissection of one of the strongest putative super-enhancers in erythroid cells. By generating a series of mouse models, deleting each of the five regulatory elements of the α-globin super-enhancer singly and in informative combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
393
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(435 citation statements)
references
References 43 publications
26
393
2
Order By: Relevance
“…However, it is very likely that many such clusters will not act as a single unit (Hay et al 2016;Shin et al 2016), and we find many of them carrying both "with" and "without" peaks (Supplemental Fig. S6).…”
Section: Wwwgenomeorgmentioning
confidence: 88%
“…However, it is very likely that many such clusters will not act as a single unit (Hay et al 2016;Shin et al 2016), and we find many of them carrying both "with" and "without" peaks (Supplemental Fig. S6).…”
Section: Wwwgenomeorgmentioning
confidence: 88%
“…Similarly, individual deletion of three constituent enhancers of the Wap super-enhancer revealed their partially redundant role in regulating transcription of Wap (Shin et al 2016). Furthermore, Hay et al (2016) showed by deletions within the Hba super-enhancer that each constituent enhancer acts independently in an additive manner to regulate expression of Hba genes in vivo. In ES cells, deletion of Dppa5aEC-Up or Dppa5aEC-Dn alone caused only a 36% and 16% reduction, respectively, in the levels of Dppa5a; deletion of both regions caused a 99% reduction.…”
Section: Enhancer and Super-enhancer Equivalencementioning
confidence: 99%
“…The SCR overlaps a predicted super-enhancer and was found to be required for >85% of the transcript levels of Sox2 in ES cells. Similarly, other studies have revealed the role of select super-enhancers in gene regulation (Mansour et al 2014;Hnisz et al 2015;Hay et al 2016;Huang et al 2016;Shin et al 2016). At the Sox2 locus, an additional super-enhancer was predicted surrounding the Sox2 gene; however, deletion of the enhancers within that region revealed that they are not required for Sox2 transcription in ES cells, thus raising questions about the super-enhancer prediction model (Zhou et al 2014).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…35 While the concept of super enhancers is relatively new and requires substantial validation, their emerging role may be important in cell identity both in health and disease. 36 …”
Section: Transcriptional Codementioning
confidence: 99%